Unemployement and Labour Force Participation : The Canadian Experience - Swidinsky, Robert (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1973)
In an analysis of the short-run sensitivity of the Canadian labour force time series regression results appear inconclusive whereas cross-section regression results suggest a strong negative response to unemployment. Generally, the findings from the cross-section are comparable neither qualitatively nor quantitatively with those from the time series.